A comparative study of egg and sperm quality of Clarias gariepinus fed Unical Aqua Feed and Coppens Commercial Feed - Eyo, Victor Oscar; Ekanem, Albert Philip; Obiekezie, Austin I. (International Journal of Biology, Pharmacy and Allied Sciences, 2012)
A comparative study of egg and sperm quality of Clarias gariepinus fed Unical Aqua feed and Coppens commercial feed was conducted for six months in concrete tanks. Fifty post fingerlings with a mean weight of 0.50±0.02kg were stocked in six experimental units (A1, A2, A3, B1, B2 and B3). Fish in units A1, A2 and A3 were fed Coppens feed while fish in units B1, B2 and B3 were fed Uncial Aqua feed twice daily at 3% of their body weight, in triplicates and controls. Proximate composition analysis of the dry matter of the two experimental feed showed that moisture, fat, crude fibre, ash, CH2OH and Caloric contents were significantly different (P<0.05) while crude protein contents, mean egg diameter (MED), mean sperm motility (MSM), mean milt density (MMD), mean sperm volume (MSV), and percentage hatchability of fish fed the two feed were not significantly different (P<0.05). Water quality parameters were within the acceptable range for fresh water fish culture during the experiment. On the basis of the results obtained, it was concluded that the egg and sperm qualities of fish fed the two experimental feed were the same. Unical Aqua feed is recommended in place of Coopens commercial feed on the basis of affordability for the production of C. gariepnus brood fish.
Keywords: Unical Aqua Feed; Coopens Feed; Eggs and Sperm Quality; Clarias gariepinus